A Distinct Malignant Epithelioid Neoplasm With GLI1 Gene Rearrangements, Frequent S100 Protein Expression, and Metastatic Potential: Expanding the Spectrum of Pathologic Entities With ACTB/MALAT1/PTCH1-GLI1 Fusions. (April 2018) - Antonescu, Cristina R.; Agaram, Narasimhan P.; Sung, Yun-Shao; Zhang, Lei; Swanson, David; Dickson, Brendan C.
Abstract : ACTB-GLI1 fusions have been reported as the pathognomonic genetic abnormality defining an unusual subset of actin-positive, perivascular myoid tumors, known as "pericytoma with the t(7;12) translocation." In addition, GLI1 oncogenic activation through a related MALAT1-GLI1 gene fusion has been recently reported in 2 unrelated gastric tumors, namely plexiform fibromyxoma and gastroblastoma. Triggered by unexpected targeted RNA-sequencing results detecting GLI1 -related fusions in a group of malignant neoplasms with round to epithelioid morphology, and frequently strong S100 protein immunoreactivity, we investigated their clinicopathologic features in relation to other known pathologic entities sharing similar genetics. On the basis of a combined approach of targeted RNA sequencing and fluorescence in situ hybridization screening, we identified 6 cases with GLI1 gene fusions, including 4 fused to ACTB, 1 with MALAT1 and 1 with PTCH1 gene. Patients had a mean age of 36 years at diagnosis (range, 16 to 79 y) and slight female predilection all except 1 tumor originated in the soft tissue. Microscopically, the tumors had a monomorphic epithelioid phenotype arranged in a distinctive nested or cord-like architecture, separated by thin septae and delicate capillary network. All except 2 cases were strongly positive for S100 protein, whereas being negative for SOX10, SMA, and EMA. Only 1 tumor showed focal cytokeratin positivity in rare cells. Although the tumors showed some resemblance to pericytic/glomus tumors or myoepithelial tumors, the immunoprofile was not supportive of either lineage. Moreover, in contrast to the benign course of so-called pericytoma with t(7;12), 3 patients in this series developed metastatic disease to either lymph nodes or lung. In fact the only patient with lung metastases showed a novel PTCH1-GLI1 gene fusion. It remains to be determined whether these tumors represent a clinically and immunohistologically distinct subset of pericytoma, or an altogether novel soft tissue sarcoma. Our findings open new opportunities for targeted therapy, as tumors with GLI1 oncogenic activation, and subsequent PTCH1 overexpression, might be sensitive to sonic hedgehog pathway inhibitors. Abstract : Supplemental Digital Content is available in the text.